Sumbangsih Juhani Pallasmaa dalam Teori Arsitektur - Stefani Natalia Sabatini; Feni Kurniati; Vika Haristianti; Iwan Sudrajat (RUAS (Review of Urbanism and Architectural Studies), 2017)
Given the condition that there is very limited discussion about Juhani Pallasmaa ideas, this study aims to discover substantial overview of Pallasmaa selected writings. This study was conducted by extracting five key writings of Pallasmaa and then complemented it by others’ writings, which also focus on Pallasmaa’s notions. The findings show that Pallasmaa ideas can be devided into several topics which are multisensoric architecture, technology and computation, cultural and historical based considerations, contextualization, and imagination in architectural design.